Toward a Sustainable Food System in West Papua, Indonesia: Exploring the Links Between Dietary Transition, Food Security, and Forests - Nurhasan, Mulia; Maulana, Agus Muhamad; Ariesta, Desy Leo; Usfar, Avita Aliza; Napitupulu, Lucentezza; Rouw, Aser; Hurulean, Ferdinandus; Hapsari, Azizah; Heatubun, Charlie D.; Ickowitz, Amy (Frontiers in Sustainable Food Systems, 2022)
Natural tropical forests cover 89% of the land area of West Papua Province, Indonesia. Forests have traditionally been an important part of local food systems for Indigenous Papuans. Despite the contribution of forests to food security, West Papua has been ranked as one of the most food-insecure provinces in Indonesia, with high rates of both under-and-overnutrition. This paper aims to discuss the dietary transition taking place in West Papua and uses local perspectives to explore the link between changes in diets, food security, and forests. We used mixed methods with a triangulation design to corroborate the quantitative data that we present from two rounds of the National Socioeconomic Survey (SUSENAS) on food consumption for West Papua from 2008 and 2017, with information from four focus group discussions with institutional and local stakeholders. The quantitative analysis showed that West Papua is experiencing a dietary transition, moving away from the consumption of traditional foods, such as sago, tubers, wild meat, and fresh legumes, toward diets with more rice, chicken, tofu, and tempeh. The consumption of processed and ultra-processed food (UPF) has increased while the consumption of fresh food has decreased. The qualitative analysis confirmed these findings. The institutional stakeholders expressed a desire for Papuans to return to eating traditional diets for better food security, whereas the local stakeholders worried about their children's high consumption of UPFs. We also found a disconnect between how food security is measured by the national Food Security Index (FSI) and the point of view of the institutional stakeholders. While the FSI indicators are more infrastructure-related measures, the institutional stakeholders link food security with the availability, accessibility, stability, and sustainability of the food sources in their surrounding environment, especially the forests. The institutional stakeholders support the commitment of the provincial government to maintain at least 70% of the forest cover in West Papua, as stated in the Manokwari Declaration although they expressed the need for more clarity on how this will impact their food security. The Indonesian government and the international community should support this initiative and carry it out with substantial input from local Papuan stakeholders.